2017
DOI: 10.1111/pace.13200
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year extractability of novel left ventricular, active fixation leads in the sheep model

Abstract: Extraction of the side helix, active fixation LV lead from the coronary veins in the sheep model is safe, without procedural complexity, and free of complications after long-term LV lead implant duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Although only limited data is available on the ease of extraction of the Attain Stability leads, the small side helix is designed to elongate and straighten with less than one pound of proximal pressure, thereby facilitating lead release from the fibrous capsule. In 10 sheep implanted up to 112 weeks with either the Attain Stability bipolar (n = 3) or Attain Stability Quad (n = 7) LV lead, extraction was successful in all cases with manual traction alone and without evidence of vascular trauma on pathologic examination 18 . Human data is limited to seven reported cases of extraction of the Attain Stability bipolar lead, the longest at 8 months post‐implant with successful removal in all cases 10,14,19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Although only limited data is available on the ease of extraction of the Attain Stability leads, the small side helix is designed to elongate and straighten with less than one pound of proximal pressure, thereby facilitating lead release from the fibrous capsule. In 10 sheep implanted up to 112 weeks with either the Attain Stability bipolar (n = 3) or Attain Stability Quad (n = 7) LV lead, extraction was successful in all cases with manual traction alone and without evidence of vascular trauma on pathologic examination 18 . Human data is limited to seven reported cases of extraction of the Attain Stability bipolar lead, the longest at 8 months post‐implant with successful removal in all cases 10,14,19,20 …”
Section: Discussionmentioning
confidence: 99%
“…In our experience, both QAF and BAF had a <1% that manual traction might straighten and elongate the helix so that the lead would be extracted without tissue damages. [20][21][22][23][24] Though most of these experiences are described after a quite short follow-up, nevertheless extractions in animals were reported to be successful even 2 years after implantation 20 and, notably, in humans, Barletta et al 21 have recently effectively extracted a 4-years old BAF. The QAF has been developed with the same mechanism as BAF but with four steroid-eluting pacing electrodes, thus combining the characteristics of the previous two (QPL and BAF) to overcome their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, BAF and QAF were specifically designed with a new fixation concept, consisting of an exposed side helix, to enable a stable lead positioning, while avoiding tissue growth in the fixation mechanism for easy lead extraction. The initial experiences, both in animal models and in humans, have shown that manual traction might straighten and elongate the helix so that the lead would be extracted without tissue damages 20–24 . Though most of these experiences are described after a quite short follow‐up, nevertheless extractions in animals were reported to be successful even 2 years after implantation 20 and, notably, in humans, Barletta et al 21 have recently effectively extracted a 4‐years old BAF.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction was not necessary during our FU for either type of lead. But even for BipolarAS, cases of easy extractability have been reported ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%